P 124 Auricular vagus nerve stimulation in subjects with major depression – Pulsatile vs. continuous stimulation. Issue 10 (October 2017) - Polak, T.; Götzelmann, M.; Katzorke, A.; M. Zeller, J.B.; Herrmann, M.J.
Abstract : Background: Conventional vagus nerve stimulation (cVNS) is approved to treat major depression. Within this context, auricular VNS (aVNS) is of increasing interest due to its non-invasiveness. Still, the question of optimum stimulation parameters has to be solved. Method: 50 subjects with major depressive disorder were stimulated over 20 min. in the area of the auricular branch of the vagus nerve. Control stimulation (CS) was done at the ear lobe. Before and after each stimulation the participants were asked to rate their actual affective state. 30 participants were stimulated continuously, while in 20 subjects, stimulation was interrupted every 5 min. for 30 s. (pulsatile stimulation). Results: Only using pulsatile stimulation, participants significantly more often rated to feel better ( F 1, 18 = 12.35 ; p  = 0.002) and to be more optimistic ( F 1, 18 = 12.24 ; p  = 0.003) after aVNS than after CS. Using pulsatile as well as using continuous stimulation, subjects indicated to be more happy ( F 1, 18 = 24.61 ; p < 0.001 and F 1, 28 = 8.03 ; p  = 0.008, resp.). Rating of pictures of the Internatonal Affective Picture System (IAPS) showed no statistical significant difference between the stimulation methods. Conclusion: Stimulating in a pulsatile way showed more difference between aVNS and CS than stimulating in a continuous way. Self rating of the emotional state by means of a visual analogue scale seems to be a reliable tool for the examination of non-invasive stimulation techniques.